Metaplastic cancers of the breast: classification, diagnosis, treatment and prognosis - Jeziorski, Arkadiusz; Bilski, Adam; Nejc, Dariusz; Jesionek-Kupnicka, Dorota; Kubiak, Robert; Piekarski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2004)
An invasive ductal breast cancer may also contain components of different tissues. Such cancers are classified as a heterogeneous group of metaplastic cancers. In a current WHO classification, metaplastic cancers are divided into two groups: purely epithelial cancers and mixed epithelio-mesenchymal cancers. A primary diagnosis of a metaplastic cancer can be made on the basis of fine needle cytology, when both components of the cancer are present in the biopsy specimen, cancer cells and metaplastic cells. However, the final diagnosis is made on the basis of pathologic examination of the resected tumor. Radiology has a little value in the differential diagnosis of metaplastic cancers as the picture of such cancers is not characteristic. Combined treatment is a treatment of choice. The majority of authors suggest combining surgery, radiotherapy and systemic therapy, according to guidelines accepted for a treatment of invasive ductal breast cancers. Surgery is the primary therapy; resection of primary tumor (mastectomy or breast conservation) is to be performed along with axillary clearance. The choice of the method of breast surgery is based on the same factors as the choice of treatment in patients with invasive ductal cancer. Prognosis for patients with metaplastic cancers is similar or worse than prognosis for patients with cancers without metaplastic component.